Sputum ADAM8 expression is increased in severe asthma and COPD. Issue 3 (March 2014) - Oreo, K. M.; Gibson, P. G.; Simpson, J. L.; Wood, L. G.; McDonald, V. M.; Baines, K. J.
Summary Background Severe asthma and chronic obstructive pulmonary disease (COPD) are chronic inflammatory airway diseases in which the mechanisms are not fully understood. A disintegrin and metalloproteinase domain 8 (ADAM8) is an enzyme expressed on most leucocytes and may be important for facilitating leucocyte migration in respiratory disease. Objective To investigate ADAM8 mRNA and protein expression in asthma and COPD and its relationship between asthma severity and inflammatory phenotypes. Methods Induced sputum was collected from 113 subjects with asthma (severe n = 31, uncontrolled n = 39 and controlled n = 35), 20 subjects with COPD and 21 healthy controls. Sputum ADAM8 mRNA expression was measured by qPCR, and soluble ADAM8 (sADAM8) protein was measured in the sputum supernatant by validated ELISA. Results ADAM8 mRNA correlated with ADAM8 protein levels (r = 0.27, P < 0.01). ADAM8 mRNA (P = 0.004) and sADAM8 protein (P = 0.014) levels were significantly higher in both asthma and COPD compared with healthy controls. ADAM8 mRNA (P = 0.035) and sADAM8 protein (P = 0.002) levels were significantly higher in severe asthma compared with controlled asthma. Total inflammatory cell count (P < 0.01) and neutrophils (P < 0.01) were also elevated in severe asthmatic sputum. Although ADAM8 mRNA was significantly higher in eosinophilic and neutrophilic asthma (P < 0.001), sADAM8 did not differ between asthma inflammatory phenotypes. ADAM8 expression positively correlated with sputum total cell count and sputum neutrophils. Conclusions and Clinical Relevance ADAM8 expression is increased in both severe asthma and COPD and associated with sputum total cell count and neutrophils. ADAM8 may facilitate neutrophil migration to the airways in severe asthma and COPD.